Introduction to the Special Issue: Best Papers Presented at the OLC 21st International Conference on Online Learning and Innovate 2016 - Anthony G. Picciano; Paige McDonald; Patsy Moskal (Online Learning, 2016)
The Online Learning Consortium (OLC) traces its roots to the Alfred P. Sloan Consortium (Sloan-C) that emerged in the 1990s when a cadre of early adapters of online learning began to coalesce into a professional community. Funded by the Alfred P. Sloan Foundation, this community embarked on a number of activities designed to promote quality in the design and implementation of online and blended learning applications. In 1995, a one-day meeting of grantees of the Alfred P. Sloan Foundation’s Anytime, Anyplace Learning Program met in Philadelphia to discuss their work and share their experiences. Ninety individuals attended this first event. This meeting grew into an annual event for the next five years. In 2001, it was decided that the event be expanded into a full conference with paper submissions and reviews, workshops, and exhibit areas. The University of Central Florida agreed to host the conference in Orlando in November. That was a fateful decision as the attack on the World Trade Center on 9/11 followed by the anthrax scare in Florida in October of that year severely limited the number of people willing to fly to Orlando to attend the conference. Still, three hundred and sixty participants attended to share and discuss research, effective practices, student services, and administrative support for online learning. Since 2001, the conference has grown and has evolved into the premiere event for presenting current ideas, research, and best practices in online learning.